2020
DOI: 10.1128/mbio.01869-20
|View full text |Cite
|
Sign up to set email alerts
|

Host Retromer Protein Sorting Nexin 2 Interacts with Human Respiratory Syncytial Virus Structural Proteins and is Required for Efficient Viral Production

Abstract: Human respiratory syncytial virus (HRSV) envelope glycoproteins traffic to assembly sites through the secretory pathway, while nonglycosylated proteins M and N are present in HRSV inclusion bodies but must reach the plasma membrane, where HRSV assembly happens. Little is known about how nonglycosylated HRSV proteins reach assembly sites. Here, we show that HRSV M and N proteins partially colocalize with the Golgi marker giantin, and the glycosylated F and nonglycosylated N proteins are closely located in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
3
24
0
3
Order By: Relevance
“…Since HRSV uses the secretory pathway to deliver viral proteins to the assembly sites at the plasma membrane [1,15,17,19,23,24], we examined the presence of virus proteins along the main components of the secretory and endosomal pathways by immunofluorescence. Our results and previous literature have shown that HRSV F and N proteins partially co-localized with markers of the secretory pathway [1,23,24]. However, it was noteworthy that in contrast to HEp-2 cells, A3.01 cells did not display an evident accumulation of SNX2 at places where the HRSV N protein is.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Since HRSV uses the secretory pathway to deliver viral proteins to the assembly sites at the plasma membrane [1,15,17,19,23,24], we examined the presence of virus proteins along the main components of the secretory and endosomal pathways by immunofluorescence. Our results and previous literature have shown that HRSV F and N proteins partially co-localized with markers of the secretory pathway [1,23,24]. However, it was noteworthy that in contrast to HEp-2 cells, A3.01 cells did not display an evident accumulation of SNX2 at places where the HRSV N protein is.…”
Section: Discussionsupporting
confidence: 53%
“…HRSV N protein was also observed to co-localize partially with the Golgi [23]. Consistent with these findings, recently we have shown that in HEp-2 cells the M and N engage partially with secretory pathway and with the retromer complex [24]. Furthermore, HRSV P protein was found partially co-localizing with endosomal vesicles [25].…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations